Immunohistological study of entheses in spondyloarthropathies: comparison in rheumatoid arthritis and osteoarthritis. Issue 4 (1st April 2001) - Laloux, L; Voisin, M-C; Allain, J; Martin, N; Kerboull, L; Chevalier, X; Claudepierre, P
Abstract : OBJECTIVE: To determine which inflammatory cell types are present in entheses from patients with spondyloarthropathy (SpA) compared with patients with rheumatoid arthritis (RA) or osteoarthritis (OA). METHODS: Enthesis specimens were obtained during orthopaedic procedures in eight patients with SpA, four with RA, and three with OA. After decalcification, the lymphocyte subsets (CD3, CD4, CD8, CD20) in the bone marrow component of each enthesis were measured by an immunohistochemical technique. RESULTS: Oedema and an inflammatory infiltrate were present in all the SpA specimens, being clearly predominant in the bone marrow component of the entheses. The density of all cell types in the bone marrow was significantly higher in the SpA group than in the two other groups. The cell type CD3+ showed the greatest difference between the SpA and RA groups, being increased fivefold in the SpA group. Within the SpA group, CD3+ cells were considerably more numerous than CD20+ cells—a difference from the RA group—and the predominant T cells were CD8+. CONCLUSION: Persistent oedema with an inflammatory infiltrate composed predominantly of CD8+ cells was noted in the entheses of patients with SpA, being predominant in the bone marrow. These results suggest that CD8+ cells may have a key role in local inflammation in SpAs.